Răspuns :
[tex]6 {(x + 6)}^{2} - 2(x + 4)(x - 1) = {(2x - 3)}^{2} + 59[/tex]
[tex]6( {x}^{2} + 12x + 36) - 2( {x}^{2} - x + 4x - 4) = 4 {x}^{2} - 12x + 9 + 59[/tex]
[tex]6 {x}^{2} + 72x + 216 - 2 {x}^{2} + 2x - 8x + 8 = 4 {x}^{2} - 12x + 9 + 59[/tex]
[tex] 6 {x}^{2} - 2 {x}^{2} - 4 {x}^{2} + 72x + 2x - 8x + 12x = 9 + 59 - 216 - 8 [/tex]
[tex]78x = - 156 \: | \div 78 [/tex]
[tex] x = - 2[/tex]
[tex]6( {x}^{2} + 12x + 36) - 2( {x}^{2} - x + 4x - 4) = 4 {x}^{2} - 12x + 9 + 59[/tex]
[tex]6 {x}^{2} + 72x + 216 - 2 {x}^{2} + 2x - 8x + 8 = 4 {x}^{2} - 12x + 9 + 59[/tex]
[tex] 6 {x}^{2} - 2 {x}^{2} - 4 {x}^{2} + 72x + 2x - 8x + 12x = 9 + 59 - 216 - 8 [/tex]
[tex]78x = - 156 \: | \div 78 [/tex]
[tex] x = - 2[/tex]